2007
DOI: 10.1589/jpts.19.83
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Anticipatory Postural Adjustments by Repetition of the Tiptoe Movement

Abstract: Abstract. The purpose of this study was to investigate the influence of repetition on anticipatory postural adjustments between two tiptoe movement tasks. Ten healthy young male (22.5 ± 2.6 years old) participated in this study. They stood on tiptoe from standing position as quickly as possible after an auditory stimulus. Single and repetitive tasks as the tiptoe movement task were performed. Electromyogram during the tiptoe movement was measured in the gastrocnemius (Gas), tibialis anterior (TA), biceps femor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Previous authors have reported that during anterior movement in the flexion phase, the plantar flexor is inhibited and the TA is activated 19) . In the present study, the highest mean TA activity, about 75.5% in FS, was directed to ankle dorsiflexion to simultaneously position the body anteriorly as the center of mass moved forward over the feet and counteracted the high risk of falling forward 9,13) . According to the findings, the tiptoe squat required higher muscular effort in the EDB.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Previous authors have reported that during anterior movement in the flexion phase, the plantar flexor is inhibited and the TA is activated 19) . In the present study, the highest mean TA activity, about 75.5% in FS, was directed to ankle dorsiflexion to simultaneously position the body anteriorly as the center of mass moved forward over the feet and counteracted the high risk of falling forward 9,13) . According to the findings, the tiptoe squat required higher muscular effort in the EDB.…”
Section: Discussionmentioning
confidence: 47%
“…It was assumed in this study that the sagittal movement primarily influences the SQ-ST movement; therefore, related muscles in the anterior and posterior lower extremities played dominant roles in the forward and backward movement as reported in the sit-to-stand pattern 9,13) . Performing a full squat put the center of mass behind the BOS; therefore, difficulties in flexing the hip and the ankle joint were related to issues of both muscle strength and the negative effects of being off balance.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These forces are created by postural muscle activity and joint movement in the lower limbs [7][8][9] . Anticipatory postural adjustments (APAs) observed in postural muscles prior to the onset of movements affect the performance of fast voluntary movements, including the reaching movement [9][10][11] . These facts suggest that it is possible to perform rapid, stable reaching with appropriate postural control delivered by the lower limbs.…”
Section: Introductionmentioning
confidence: 99%
“…As a counterbalance, the heel is lifted, which shifts the head of the metatarsophalangeal to the point of rotation and therefore places the thigh almost parallel to the floor. This is known as the "tiptoe" posture which is performed by shifting the body weight to the head of the metatarsophalangeal joint (Muray et al, 1967;Saito et al, 2007).…”
Section: Introductionmentioning
confidence: 99%